UPAYA MENINGKATKAN KETERAMPILAN BERFIKIR KRITIS DAN HASIL BELAJAR PESERTA DIDIK MELALUI PEMBELAJARAN KOOPERATIFTIPE THINK TALK WRITE (TTW) PADA MATA PELAJARAN EKONOMI MATERI BANK SENTRAL EKONOMI KELAS X-I IPS SMAN JOGOROTO JOMBANG 2019/2020 - parwati, hartining (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2020)
ABSTRACT Parwati, Hartining, 2020. The Improvement Critical Thinking Skills and of economic Test Student Learning by Cooperative Learning Type Think Talk Write atten grade class high school Jogoroto jombang. SMAN JOGOROTO Jombang. Keywords : Cooperative Learning type TTW , critical thinking activityand the result of students learning. Economics is always assumed difficulty by students. So that way, the teachers must be effective to choosethe approach of learning. One of learning that use is cooperatif type TTW. This research was held on the 1st semester of ten grade high school Patriot year 2019/2020 with number 32 students. This research use techniq to collect observation of test studentslearning. . The result of research show that students activity of learning process of cycle show inproving from first cycle, to focuson the teacher's explanations by 77%, 80% asking questions, active indiscussion 88.5%, and make summary 83.3% .the result of first cycle 1 is about 65.59 with 66%, second cycle 88.5 with 100%. so, learning through cooperative learning type TTW with bank central can improve the result of students learning ten grade class High School Jogoroto jombang academic year 2019/2020.